Herpes simplex virus type-2 stimulates HIV-1 replication in cervical tissues: implications for HIV-1 transmission and efficacy of anti-HIV-1 microbicides - Rollenhagen, C (Nature Publishing Group, 2014)
Herpes Simplex virus Type-2 (HSV-2) increases the risk of HIV-1 acquisition, yet the mechanism for this viral pathogen to regulate the susceptibility of the cervicovaginal mucosa to HIV-1 is virtually unknown. Using ex vivo human ectocervical tissue models, we report greater levels of HIV-1 reverse transcription, DNA integration, RNA expression, and virions release in HIV-1/HSV-2 co-infected tissues compared with HIV-1 only infected tissues (P<0.05). Enhanced HIV-1 replication was associated with increased CD4, CCR5, and CD38 transcription (P<0.05) and increased number of CD4(+)/CCR5(+)/CD38(+) T cells in HIV-1/HSV-2 co-infected tissues compared with tissues infected with HIV-1 alone. Tenofovir (TFV) 1% gel, the leading microbicide candidate, demonstrated only partial protection against HIV-1, when applied vaginally before and after sexual intercourse. It is possible that mucosal inflammation, in particular that induced by HSV-2 infection, may have decreased TFV efficacy. HSV-2 upregulated the number of HIV-1-infected cells and elevated the concentration of TFV needed to decrease HIV-1 infection. Similarly, only high concentrations of TFV inhibited HSV-2 replication in HIV-1/HSV-2-infected tissues. Thus, HSV-2 co-infection and mucosal immune cell activation should be taken into consideration when designing preventative strategies for sexual transmission of HIV-1.